PERAN EKSISTENSI SAHAM DI LQ45 PADA KINERJA PROFITABILITAS PERUSAHAAN - Herman Karamoy; Hizkia H. D. Tasik (EKUITAS (Jurnal Ekonomi dan Keuangan), 2019)
Many companies in Indonesia compete to improve the financial performance to be listed in LQ45 index. LQ45 index is the house of 45 stocks with high liquidity, big market capitalization and good financial performance. This paper aims to investigate whether the existence status of stocks in LQ45 index in the past affects the current profitability performance of the companies. This study relies on semesterly data from 19 companies dated from 2012 to 2015. Using panel data regression model of Net Profit Margin (NPM), the findings suggests that the existence of stocks in LQ45 index in previous period significantly affect the NPM. The results are robust and consistent across specifications either using fixed effect or random effect approaches. The magnitude ranges from 22,77 to 26,87 percentage points.